Motivasi dan Minat Siswa SMP Terhadap Pencak Silat - Candra Aldi Cahyono; Bahtiar Hari Hardovi; Ahmad Bahriyanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to describe the motivation and interest levels of students at SMP PGRI 2 Tempurejo towards pencak silat as a sport and cultural heritage. The study used a descriptive quantitative approach, involving 28 eighth-grade students as a sample selected through purposive sampling. The research instrument was a questionnaire with 12 statements (6 positive and 6 negative) using a four-choice likert scale. Data were analyzed using percentages. The results showed that students had a positive attitude towards pencak silat, as indicated by the highest scores for pride (82.14%) and recognition of positive values ​​(80.36%). The overall index of 73.07% indicates the